Treatment experience for different risk groups of Kaposiform hemangioendothelioma - Li, Miaomiao; Wang, Xusheng; Kieran, Rosalind; Sun, Zheng Wei; Gong, Yubin; Lei, Hongzhao; Sun, Bin; Xiao, Li; Wang, Yanlin; Wang, Song; Li, Zhiyu; Wang, Luying; et al. (Frontiers in Oncology, 2024)
Kaposiform haemangioendothelioma (KHE) is a rare vascular tumor with a high risk of mortality. Few studies with large samples of KHE have reported. KHE may develop into Kasabach-Merritt phenomenon (KMP), which characterized by thrombocytopenia and consumptive coagulopathy. The features of severe, symptomatic anemia and life-threatening low-platelets, make the management of KHE associated with KMP challenging. To examine the clinical characteristics of patients with KHE and discuss the treatment experience for different Risk Groups of Kaposiform Haemangioendothelioma. We review 70 patients diagnosed with KHE between 2017 and 2022 in our center, we classify lesions into three Clinicopathological Stages and three risk levels. In our cohort, 27% were neonates, KHE lesion occurred at birth in 84% of patients. Common clinical characteristics included a locally aggressive cutaneous blue-purple mass (89%), thrombocytopenia (78%), associated coagulation disorder (100%), local pain or joint dysfunction (20%). 78% of our cohort patients developed KMP. 92% patients were given surgery treatment and 89% of these patients were given high dose methylprednisolone (30mg/kg daily) before surgery. In 55 patients with KMP, 36% of them were sensitive to high dose corticosteroid therapy. Patients of Low-Risk Grade (8 cases) all underwent operations, all of them recovered without recurrence after maximum of 5 years follow-up. 25 out of 26 patients of High-Risk Grade underwent surgery treatment, with 1 case underwent secondary surgery after recurrence, 1 case took Sirolimus. 32 out of 36 cases in High-Risk Grade underwent surgery (include 2 cases underwent external carotid artery ligation and catheterization), 3 of them underwent secondary operation after recurrence, remaining 4 cases took medicine. The mean length of having Sirolimus was 21 months. 2 cases died at one and three months after discharge. Our study describes the largest assessment of high-risk KHE patients who have been given an operation to date, with five years following up track of recovery, which provides an invaluable experience for the future treatment of KHE and KMP patients from different risk groups: Early surgical intervention may be the most definitive treatment option for most KHE patients; Multimodality treatment is the best choice for the most life-threatening Extremely High-Risk Group.